2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Farm Labor Contractor Registration and Testing [State] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
Farm labor contractor registration and testing regulations establish state standards and registration procedures for farm labor contractors (crew chiefs) operating in the State of Florida. This is EDIS document FE397, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.